Saturday

March 28, 2015

March 28, 2015

Posted by **Steven** on Sunday, June 25, 2006 at 6:51pm.

Solve -5x - 6 = -6x^2

Rearrange to

6x^2-5x-6=0

(3x + 2)(2x - 3)= 0

Set each factor equal to zero and solve for x. I hope this helps.

**Answer this Question**

**Related Questions**

Math Repost!!Please Help!!!! - 6-y --------- y^2-27-24 well it should simplify ...

Math - I dont understand this!!! If rstv=1 and stuv=0, which of the followin ...

help...solving a polynomial....algebra - solve this please....help me....12x(...

Algebra II - I need some help with some problems as well as need some checked. ...

algebra - It is not solvable by that method, shanaid. You have to get all the ...

Math - I just don't understand this question: h(t)=A*b^x h(3)=4 h(5)=40 Solve ...

MATH - HOW DO I SOLVE A QUADRATIC EQUATION BY FACTORING? Do you have a specific ...

algebra - x+1 -x+2 = x+3 ____ _____ ____ 2 3 4 How do I solve this equations? ...

why is noone answering my question?!?! - A rational function that passes through...

algebra - 3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals ...